USAID invests USD$30 million in scaling up of Participatory Rangeland Management (PRM) in Ethiopia - CGIAR Research Program on Livestock (2020)
Participatory rangeland management (PRM) is an innovation developed by ILRI and partners in Ethiopia. USAID is investing USD$30 million in scaling up PRM through its Resilience in Pastoral Areas project.